2019
DOI: 10.1039/c8nr10043h
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the self-assembly of a tripeptide for the formation of antimicrobial surfaces

Abstract: The self-assembly of a tripeptide into particles with different morphologies is described along with the particles application as antibiofouling and antimicrobial coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 57 publications
6
45
0
Order By: Relevance
“…Understanding the interaction of the peptide-coated surfaces with water is essential as both hydrophobicity and hydrophilicity play a signicant role in the design of smart and efficient antifouling materials. 35 It was observed that the hydrophobic nature of the peptide-coated surfaces was increased compare to that of the bare surface. The increased hydrophobicity of the Teon-like layer coated surfaces was conrmed by contact angle measurements with water droplets.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the interaction of the peptide-coated surfaces with water is essential as both hydrophobicity and hydrophilicity play a signicant role in the design of smart and efficient antifouling materials. 35 It was observed that the hydrophobic nature of the peptide-coated surfaces was increased compare to that of the bare surface. The increased hydrophobicity of the Teon-like layer coated surfaces was conrmed by contact angle measurements with water droplets.…”
Section: Resultsmentioning
confidence: 99%
“…These include hydrophilic polymer coatings and hydrogels, such as those based on poly(ethylene glycol) (PEG) and zwitterionic polymers among others [9][10][11][12][13][14][15][16][17][18][19] , as well as superhydrophobic surface coatings 3,20 , and those based on low-fouling surface topographies, such as those that mimic shark skin 21,22 or other natural low-fouling patterns 23 . Furthermore, others have attempted to combine these materials with components that have active antimicrobial properties, such as to prepare materials with two synergistic mechanisms; fouling resistance plus antimicrobial properties 5,24 www.nature.com/scientificreports/ polymer-metal composite materials, attention has also turned towards using enzymes as an active proteindegrading or antimicrobial component [25][26][27] . For example, Chiao and co-workers developed PEG-based hydrogel coatings with immobilized protease, which showed resistance towards fouling by model proteins using two synergistic mechanisms; both the intrinsic low-fouling properties of the PEG material and enzymatic protein degradation 28 .…”
Section: Honey-inspired Antimicrobial Hydrogels Resist Bacterial Colomentioning
confidence: 99%
“…developed self-assembled tripeptide particles, which reduced Escherichia coli colonization when adhered to a surface. These were co-assembled with GOx to prepare surfaces with both antimicrobial and low-fouling properties 26 . Whilst these materials were highly effective in the short term, no discussion regarding the long-term stability of the coating was included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular self-assembly has attracted extensive interest in the construction of antimicrobial and antifouling agents [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Self-assembly is a spontaneous process in which the molecular organization of diverse building blocks, including nucleic acids, peptides, proteins and lipids, organize into well-ordered structures at the nano-scale [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the specific building blocks and the assembly conditions, various nano-structured morphologies, including fibrils, tubes, sheets, tapes, spheres, vesicles and hydrogel matrices, can be formed in vitro, allowing for distinctive functional possibilities [ 28 , 30 , 31 , 32 , 33 , 34 , 35 ], mainly in tissue engineering [ 36 , 37 , 38 , 39 ], regenerative medicine [ 40 ], cell culture [ 41 , 42 , 43 , 44 ], drug delivery [ 36 , 39 , 45 , 46 , 47 , 48 , 49 ], bio-imaging [ 50 , 51 ] and fabric functionalization [ 52 ]. Coatings based on self-assembled peptides, primarily for antibacterial purposes, have been recently reported [ 5 , 12 , 13 , 21 , 53 , 54 , 55 , 56 ]. The self-assembly of the tri-peptide DOPA-Phe(4F)-Phe(4F)-OMe into an antifouling coating by the dip-coating technique was reported [ 13 ].…”
Section: Introductionmentioning
confidence: 99%